Thermodynamic properties and phase behaviour of biodiesel fuels derivatives - Tang, Yi Jiang (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
This project, thermodynamic properties and phase behavior of biodiesel fuels derivatives for engine technology, was mainly focusing on the study and the development on the basisod modern theory, a simple and effective way to predict phase equilibra, data and thermodynamic propertiest of binary systems formed by a methyl ester and an alcohol.Little information is available on the vapor-liquid equilibra(VLE) of methyl + alcohol system.